Avaliação do emprego do pantoprazol na proteção renal em ratos submetidos à lesão renal por isquemia/reperfusão sob anestesia inalatória com isoflurano - Santos, João José Borges de Barros dos [UNESP] (2015)
Background and Objective: acute kidney injury (AKI) determines an increase in morbidity and mortality of hospitalized patients. Early diagnosis and the realization of renal protection measures are essential. It was observed that pantoprazole has effect similar to ischemic preconditioning in rat hearts, promoting protective effect. The objective was to analyze the use of pantoprazole in protecting kidneys subjected to ischemia and reperfusion in rats under inhalation anesthesia with isoflurane. Method: forty rats, Wistar male rats, were randomly divided into four groups: RIP (pantoprazole + left renal ischemia), P (pantoprazole), IR (left renal ischemia) and Sham. Renal ischemia time was 20 minutes and reperfusion 30 minutes. The anesthetic technique performed: inhalation anesthesia with isoflurane. The pantoprazole dose was 192 mcg/kg. All animals underwent right nephrectomy and at the end of the experiment proceeded to left nephrectomy for subsequent histological evaluation and classification through tubular necrosis scale. The parameters were: mean arterial pressure (MAP), rectal temperature, the criteria of RIFLE and AKIN, urinary dosage of biomarkers NGAL, KIM-1 and IL-8 and histological evaluation. Serum creatinine was collected in three moments: M1, after monitoring, M2, and M3 after reperfusion, 24 hours after the beginning of the experiment. The urine samples to test for biomarkers occurred before (Urine 1) and after the experiment (Urine 2). The attributes were subjected to statistical analysis and differences were considered statistically significant when p <0,05. Results: significant differences were observed between the groups with application of RIFLE criteria (p=0.007) and AKIN (p=0.003). The PIR and IR groups evolved with higher incidence of AKI. The NGAL and KIM-1 biomarkers increased in all groups throughout the experiment, but with higher values in the PIR and IR groups. IL-18 revealed no group effect (p=0.38) nor the ...